THE INDICATOR OF STABILITY OF FUNCTIONING OF THE COMPLEX MEDIA OF THE AUTOMATED SYSTEM OF AIR TRAFFIC CONTROL - E. A. Bolelov; K. N. Matyukhin; N. N. Mailov (Научный вестник МГТУ ГА)
The article discusses the concept of information and technical state media, which is part of the automated system of air traffic control, as well as the definition of stability of functioning of the complex and a method of forming a resilience index.